EDUKASI GIZI KEBERHASILAN MENYUSUI PADA MASA 1000 HARI PERTAMA KEHIDUPAN - Silvia Mawarti Perdana; La Ode Reskiaddin; Vinna Rahayu Ningsih (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2023)
Breast milk (ASI) is the main food and drink needed for children aged 0-6 months. At the age of children 6 months to 2 years, breastfeeding needs to be supplemented with complementary foods (MP-ASI). The mother's inability to breastfeed from birth to at least two years of age is caused by several factors, including limited breastfeeding techniques, and imbalanced consumption patterns during pregnancy and breastfeeding, thereby reducing the quantity and quality of breast milk. In this community service activity, nutritional education related to breastfeeding techniques and balanced consumption patterns that support the success of breastfeeding in the first 1000 days of life has been carried out with the target of members of the Indonesian Breastfeeding Mothers Association (Aimi) Jambi Region. Community service activities carried out include: (1) nutrition education related to breastfeeding techniques and balanced nutrition patterns; and (2) a demonstration of the processing of nutritionally balanced foods and beverages to produce quality and high-quality breast milk. There was a significant difference in the participants' knowledge compared to before the nutrition education (test score from 60 to 92).